(untitled) (Research, Society and Development, 2022)
Objectives: To identify the epidemiological profile of ischemic and hemorrhagic stroke in young patients between the years 2008 and 2021. Methodology: This is an epidemiological, retrospective and descriptive study based on data obtained from the Hospital Information System of the Department of Informatics. of the Unified Health System (SIH/DATASUS). Results: There were 87,897 hospitalizations for stroke in the age group 15 to 39 years in the period between January 2008 and July 2022 and there was a mortality rate of 10.58 in this time interval. In addition, it was possible to observe that the most affected age group was from 30 to 39 years old, with 67.03% of cases, followed by the population from 20 to 29 years old with 26.33% and, finally, from 15 to 19 years old. with 6.64% of patients affected. Regarding gender, females showed the highest number of affected with 54.56% of the total. Furthermore, the number of deaths from the disease was 6,911 patients (8.2% of cases), with 2008 having the highest number with 703 cases. Finally, there was a gradual increase in the prevalence of stroke in the population analyzed between 2008 and 2021. Conclusion: There was an increase in the incidence of stroke in young Brazilians, with the most affected population being the age group from 30 to 39 years. According to Zétola (2001), this increase may be associated with changes in lifestyle that have occurred in recent years, where young people have more cases of obesity, diabetes and hypertension than in the past.